Elaboração de projeto de habitação unifamiliar a partir dos princípios de construção sustentável - Watanabe, Tiago Makoto (2013)
Within the field of single-family housing, sustainable construction has great application possibilities, because it is possible to explore its fundamental proposal in small groups self-organized. Aiming at the real applicability of the constructive techniques of the unconventional type, it was developed design in a single family dwelling, in which theory and practice inhabit the same space, while the rationality free function to separate and organize ideas more prevalent. In this study, there are discussions of bioclimatic architecture, rainwater harvesting, domestic wastewater treatment by root zone, solar heater, woodframe structure and green roof. The main data produced can be found in the search results, which lead to the appendices, which contains the drafts prepared. As a conclusion, it is possible the real applicability of the techniques and the benefits of continuing development of this knowledge.